PSYCHO-EMOTIONAL STATES AND STRESS TOLERANCE IN SPORTSMEN - Saidov, G.K.; Akhmedov, N.Sh. (Educational Research in Universal Sciences, 2023)
Forming a healthy lifestyle in society, strengthening the health of the population, raising a physically healthy and spiritually rich young generation, creating conditions for citizens to seriously engage in physical education and sports are considered to be the most urgent issues of today. One of the main means of bringing up the younger generation is sport. In order to participate in sports competitions, it is necessary for athletes to have perfect preparation from a psychological point of view, in order to perform the technical elements correctly and to show a good result at the same time.